(untitled) (Laisvalaikio tyrimai, 2018)
Research background. The article discusses the possible ways of solving systemic problems of Sochi city popularization as a year-round resort, which confirms the need for the development of the unified state promotion policy of Sochi city as a unique republic`s property, the place where Russia’s Olympic and Paralympic Winter Games were grandly held for the first time. The state promotion policy should be based on the combination of institutional and project-based approaches, the development of cooperation between all levels of governmental structures, the business community and civil society organizations and aimed at implementing the priorities within the framework of each strategic direction. The object of research was the tourist market of Sochi resort and mass sports entertainment events. The purpose of research was an assessment of the impact of mass sports entertainment events on the tourism development in the region. Methods. The authors used a set of general scientific (analysis, synthesis, comparison, generalization) and specifically – scientific (theoretical) research methods. The quantitative impact assessment was carried out by analysing the volume of tourist flow, the passenger traffic of Adler airport, the availability of hotels and a number of other indicators, including the dynamics of gross regional product. Results. The preparation and holding of major international sporting and cultural events will be certainly based on the experience gained during the Olympic Games 2014. The construction of new and reconstruction of existing sports facilities required for the successful conduct of these activities will also contribute to further development of the infrastructure of sports facilities. And this, in turn, will provide Russian Federation with a further strengthening of the status of a leading sports power. Conclusion. These directions give the possibility to use effectively objects after the Games due to the formation of modern venues, most of which have no analogues on the territory of modern Russia, which, of course, is not only a long term investment in the development of professional sports in Sochi, but in the tourism industry in Russian Federation as a whole. Sochi tourist and recreational clusters represent themselves a set of interrelated objects of recreational and cultural orientation, collective means of accommodation, catering and related services provided the necessary infrastructure available in the modern city of Sochi. In short terms the result will be the satisfaction of needs of different categories of Russians, as well as foreign citizens, active and fulfilling rest, health promotion using balneology resources of Sochi, joining a growing number of sports and recreational as well as cultural events held in Sochi city. The tourism as an industry, stimulating economic development, can be used as an instrument of Russian state policy to optimize economic development. Due to the Olympic Games 2014 we can observe the improvements and significant changes in the Russian sphere of tourist services. According to the forecasts of tour operators the demand for rest in Sochi by different estimates has increased from 15 to 40 % (on the date 15.05.2014). The emergence of new possibilities for the practice of tourism and promotion of winter sports will be aimed at improving the image of Sochi city, which together can provide the significant economic benefits. Keywords: Sochi city-resort, steady growth, heritage games, MICE-tourism, entertainment event.